Hybrid M-ary in braided single stage approach for multiphoton quantum secure direct communication protocol - Harun, Nur Ziadah; Ahmad Zukarnain, Zuriati; Mohd Hanapi, Zurina; Ahmad, Idawaty (Institute of Electrical and Electronics Engineers, 2019)
Quantum secure direct communication (QSDC) is a branch of quantum cryptography whichnexploits laws of physics and was recently proposed for securing information transferred from sender to receiver without relying on computational complexity. Instead of an entangled photon, the quantum cryptography employs two other approaches, single photon and multiphoton for encoding the messages. The multiphoton was proposed to outperform the weaknesses of a single photon by introducing the multiplicity of a photon to perform data encryption tasks. Despite the advantages of multiphoton, the transmission time to transfer the encoded data is still regarded as a critical issue. Most of the multiphoton approaches require multiple photons to travel along a number of stages. Moreover, extra time is needed to change the polarization angle of the optical device for encoding purposes. These situations have resulted in an increase in source redundancy, which subsequently leads to an increase in the transmission time. In this paper, a compression message approach is proposed to mitigate the substantial increase in time used for the data transmission processes. The proposed compression approach, namely, hybrid M-ary in a braided single stage (HMBSS) is based on the lossless data encoding such that the number of photons is reduced in the data transmission stage. Extensive simulation experiments have been conducted to test the performance of the proposed approach against some selected multiphoton approaches. The results show that the proposed approach outperforms braided single-stage, M-ary three-stage and initialization vector in terms of reducing total average transmission time to encode the photon by about 75.9% and 91.7%, respectively. Furthermore, the HMBSS reduces the overhead on the transmission channel by minimizing the number of message's bits by about 45% in average even when the length of the message increases during the transmission as compared to others.